Prolapse of inverted ileal loops through a patent vitellointestinal duct. (22nd October 2015) - Pathak, Ashish; Agarwal, Nitin; Singh, Poonam; Dhaneria, Mamta
Abstract : We report a case of a prolapsed patent vitellointestinal duct (PVID) in a 2-month-old girl child who presented with sudden increase in size of a polypoidal lesion into a large, 'Y'-shaped reddish, prolapsing lesion, discharging gaseous and faecal matter at her umbilicus. The lesion was diagnosed as a prolapse of inverted ileal loops through the PVID. The child had no associated congenital anomalies. A transumbilical exploration was performed, followed by wedge resection and anastomosis. The child tolerated the procedure well and the postoperative course was uneventful. If the omphalomesenteric duct fails to obliterate a range of congenital defects related to the umbilicus, it can become clinically apparent. Meckel's diverticulum is the commonest of these defects but is most often asymptomatic. PVID is the most common symptomatic anomaly of the patent omphalomesenteric duct and requires prompt surgical correction to avoid complications.